Uwarunkowania prawne funkcjonowania przedsiębiorstwa windykacyjnego - Dańczak, Renata (Legal Regulations of a Debt Collection Enterprise, 2005)
The present article discusses the most important changes, introduced into the Polish legal system, which have an impact on the work and activities of the debt collection enterprise. As the extent of the article is limited, the choice of regulations discussed in it is subjective. It mainly presents changes caused by three acts - the law on economic activities, the statute on the National Court Register and the Code of Commercial Companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 151-163